Determinasi faktor-faktor manajerial terhadap kinerja guru: Studi pada guru matematika SMK Negeri di Kabupaten Bantul - Nodo Nodo; Mansur Mansur (Journal of Education Policy and Management Studies, 2025)
This study aims to determine the simultaneous effect of work motivation, principal's academic supervision and job satisfaction on the performance of mathematics teachers at State Vocational Schools in Bantul Regency. Meanwhile, it specifically aims to analyze the effect of work motivation on teacher performance, the effect of principal's academic supervision on teacher performance and the effect of job satisfaction on teacher performance. This type of research is quantitative with a population of 59 teachers. The data collection technique used a questionnaire in the form of a questionnaire. The data analysis technique used multiple regression analysis and partial correlation analysis. The results of this study indicate that (1) there is a positive and very significant influence jointly between work motivation, principal's academic supervision and job satisfaction on teacher performance, (2) there is a positive and very significant influence between work motivation on teacher performance, ( 3) there is a positive and very significant effect between the principal's academic supervision on teacher performance and (4) there is a positive influence between job satisfaction on teacher performance. Of the three independent variables that have a dominant influence on the performance of State Vocational High School mathematics teachers in Bantul Regency, the teacher's work motivation.